2007
DOI: 10.1002/cbdv.200790042
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Genetic Differentiation of Ligularia tsangchanensis in Yunnan and Sichuan Provinces of China

Abstract: The intraspecific diversity in L. tsangchanensis collected in the Chinese Provinces Yunnan and southwestern Sichuan was studied by chemical and genetic approaches. The samples collected in Yunnan were found to contain cacalol (1) as the sole major component, while samples from Sichuan contained 7alpha- and 7beta-eremophila-9,11-dien-8-one (5 and 6) as well as the 3alpha-angeloyloxy derivative 7 as major components. In addition, the sequences of the internal transcribed spacers (ITSs) of the ribosomal RNA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Cacalol has been isolated from various medicinal plants including Cacalia delphiniifolia, which is a popular edible wild plant in Asian countries [20,21]. Cacalol was also identified as major anti-hyperglycemic and anti-inflammatory sesquiterpene in the aqueous extract from the roots of Psacalium decompositum, which has been used as a traditional medicine in Mexico and the Southwestern United States for the treatment of rheumatism, fever, skin infections and ulcers, diabetes and tumors [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Cacalol has been isolated from various medicinal plants including Cacalia delphiniifolia, which is a popular edible wild plant in Asian countries [20,21]. Cacalol was also identified as major anti-hyperglycemic and anti-inflammatory sesquiterpene in the aqueous extract from the roots of Psacalium decompositum, which has been used as a traditional medicine in Mexico and the Southwestern United States for the treatment of rheumatism, fever, skin infections and ulcers, diabetes and tumors [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Cacalol has been isolated from various medicinal plants including Chinese herbs Ligularia tsangchanensis and Roldana angulifolia as well as Psacalium. decompositum, which is widely used as a traditional medicine in Mexico and the Southwestern United States for the treatment of rheumatism, fever and ulcers [110][111][112][113][114]. A sesquiterpene derivative has also been patented recently which has anti-tumor effects [115].…”
Section: Cacalolmentioning
confidence: 99%
“…(Asteraceae) in the Hengduan Mountains area provides interesting samples for the study of plant diversity, since the genus is highly diversified and their genetic differentiation is considered to be still continuing in the area. The chemical and genetic diversity of some Ligularia species has been investigated by chemical constituents and DNA sequences for exploring its speciation and evolution (Nagano et al 2007(Nagano et al , 2006Kuroda et al 2007;Torihata et al 2007;Hanai et al 2005). In order to devise adequate genetic diversification, conservation, and management strategies for Ligularia species, we developed microsatellite markers (SSR) from Ligularia hodgsonii using the Fast Isolation by AFLP of Sequences Containing repeats protocol (FIASCO) (Zane et al 2002); at the same time, no nuclear microsatellite primers have been reported for Ligularia.…”
mentioning
confidence: 99%